The Relationship between Subjective Vitality and Big Five Personality Traits among students at King Faisal University - Yaseen, Mahmoud Mohamed Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the relationship between subjective vitality and the five major factors of personality, the study used the descriptive approach, and the study sample consisted of 127 students from King Faisal University in Al-Ahsa. The Arabization of Elsayed Muhammad Abu Hashem 2007), and the results of the study revealed the existence of a statistically significant correlation between the subjective vitality and the five major personality factors among university students, and it is also possible to predict the subjective vitality by the five major personality factors among university students. In addition, there were no differences in the subjective vitality of university students due to gender, specialization, or socio-economic level, and there were no differences in the five major factors of personality among university students due to gender, or specialization, while there were differences in openness and extroversion among university students due to the social level. Economic (low medium high).
Keywords: subjective vitality; university students; the five major factors of personality; the Kingdom of Saudi Arabia